Diagnostic Value of D-Dimer in Acute Myocardial Infarction Among Patients With Suspected Acute Coronary Syndrome - Reihani, Hamidreza (Cardiol Res, 2018)
BACKGROUND: The role of D-dimer as a diagnostic marker in myocardial infarction (MI) and acute coronary syndrome (ACS) is still a question. The aim of this study was to evaluate the diagnostic value of D-dimer in the diagnosis of AMI in patients suspected with ACS. METHODS: This cross-sectional study was conducted on patients suspected with ACS. Serial standard 12-lead electrocardiogram (ECG), D-dimer, and troponin tests were done for all the patients. According to the examinations, ECG changes, and troponin, patients were allocated into two groups of MI and unstable angina (UA). Chi-square, independent t-test, and Pearson correlation test were used by SPSS ver, 17. Cut-off point of D-dimer for MI diagnosis was evaluated by receiver operating characteristic (ROC) curve analysis. RESULTS: Seventy-five patients with a mean age of 63.1 ± 9.75 years were studied in two groups of MI (n = 34) and UA (n = 41). Patients were homogeneous based on age, gender, and risk factors for diabetes and dyslipidemia. D-dimer in patients with MI patients was higher than in patients with UA (P = 0.001). The optimal cut-off point of D-dimer for diagnosis of MI was 548 mEq/L with sensitivity and specifity of 63.4% and 91.2%, respectively. CONCLUSIONS: Based on the results of this study, it seems that the measurement of D-dimer serum level can be appropriate as a marker with high sensitivity and relatively high specificity for differentiating MI from UA in patients with suspected ACS.